Efektivitas Aplikasi SAKTI Dalam Digitalisasi Pelaporan Bendahara Pengeluaran di KPPN Surakarta - Farhan Taufik Dwihaikal; Rukmini Rukmini (Jurnal Akuntansi dan Pajak, 2025)
Adjustments are things that must be done by various sectors as a result of the Covid-19 pandemic, including the financial sector. Many activities that were previously carried out face-to-face have switched to digital through applications. This aims to limit physical contact to reduce the spread of the Covid-19 virus. In addition, we are currently entering the era of industry 4.0 which encourages changes in technology and information from manual to digital form or better known as digitalization. For example, activities in the financial sector that have implemented digitalization are reporting on the accountability of the expenditure treasurer. KPPN as a work unit that verifies the treasurer's accountability report every month implements the LPJ submission system to be online, utilizing various applications such as email, messages, etc. Following up on this situation, Direktorat Jenderal Perbendaharaan continues to develop the SAKTI application with the aim that it can be used by all task forces in the management and accountability of the State Budget. In 2022, the Ministry of Finance began implementing SAKTI to be used by all task forces in Indonesia. One of the SAKTI users, the Expenditure Treasurer, focuses on the SAKTI Treasurer Module in administering and compiling the Expenditure Treasurer's LPJ. The purpose of this study is to find out the use of the SAKTI application by the expenditure treasurer, the process of preparing the Expenditure Treasurer's LPJ, and the benefits and obstacles faced by KPPN Surakarta in making and reporting the Expenditure Treasurer's LPJ. The research method used is a descriptive qualitative research method with data collection using direct observation, literature studies and documentation. The results of the study show that the application of the SAKTI application to the digitization of expenditure treasurer reporting is considered effective.